Randomised Controlled Trials for the Evaluation of the CAP: Em-pirical Evidence about Acceptance by Farmers - Ulrich B. Morawetz; Christoph Tribl (German Journal of Agricultural Economics (GJAE), 2020)
To conduct a randomised controlled trial (RCT) to evaluate the Common Agricultural Policy it would be necessary to exclude a random selection of farms from participation. This exclusion might limit the acceptance of RCTs. We assess the acceptance of an innovative alternative RCT called the 'unconditional payment RCT' (upRCT). UpRCTs allow for the evaluation of the impact of policy measures in which farmers receive a payment conditional on the adoption of farm management practices (e.g., agri-environment-climate measures). We surveyed Austrian farmers who participated in the 'refrain from silage' measure to compare the acceptance of a conventional RCT and an upRCT using thought experiments. The acceptance of the farmers was between 18% and 51%, and the treatment effects of both variants were of comparable size. Our survey suggests that acceptance of the upRCT is about twice as high as the acceptance of the conventional RCT. We discuss that upRCTs are useful when a new measure is introduced or when the upRCT is conducted for several years.
Keywords: 330